Recent advances in researches on the innate immunity of shrimp in China - Li, Fuhua; Xiang, Jianhai (Developmental and comparative immunology, 2013)
► Research progress in shrimp immunology in China. ► The outline of shrimp humoral immune responses was suggested. ► Cellular immunity were regarded playing crucial roles in shrimp responsive to WSSV infection. The annual production of shrimp culture in mainland of China has been over one million tons for several years. The major cultivated penaeidae species are Litopenaeus vannamei, Fenneropenaeus chinensis, Penaeus monodon and Marsupenaeus japonicus. Due to the importance of shrimp aquaculture in China, researchers have paid more attention to the molecular mechanism of shrimp disease occurrence and tried to develop an efficient control strategy for disease. This paper summarizes the research progress related to innate immunity of penaeid shrimp made in the last decade in Mainland China. Several pattern recognition receptors, such as lectin, toll, lipopolysaccharide and β-1,3-glucan binding protein (LGBP) and tetraspanin were identified. The major signal transduction pathways, including Toll pathway, IMD pathway, which might be involved in the immune response of shrimp, were focused on and most of the components in Toll pathway were identified. Also, cellular immune responses such as phagocytosis and apoptosis were regarded playing very important roles in anti-WSSV infection to shrimp. The molecules involved in the maintenance of the immune homeostasis of shrimp and the progress on molecular structure and pathogenic mechanism of WSSV were summarized. Therefore, the brief outline about the immune system of shrimp is drawn based on the recent data which will help us to understand the immune responses of shrimp to different pathogens.